Pathogenetic properties of immune status at chronic viral hepatitis B and C in children - Rikalo, N (Annals of Mechnikov’s Institute, 2020)
In pathogenesis of chronic viral hepatitis (CVH) B and C in children, there are distinct immune disorders. Purpose: to provide the pathogenic characterization of parameters of cellular and humoral immunity in children with CVH B and C, depending on the phase of viral replication and inflammatory activity. Materials and methods. An immunological study of peripheral blood of 50 children with CVH B and C, aged 1 to 18 years prior to the appointment of a specific antiviral treatment were conducted. We determined the CD3+, CD4+, CD8 +, CD16+, CD22+, CD25+ cell’s population and concentration of IgA, IgM and IgG. Results and discussion. The significant decrease of CD3+ (in 10,3 %) and CD4+ (in 22%) in the phase of viral replication, indicating a persistent shortage of cellular immunity were established. The increase of CD8+ (in 12,5%) indicate the activation of cytotoxic reactions. In patients with the virus in the phase of integration or latent stage population of CD16+ were reduced in 31%, indicating inhibition of cytotoxic responses aimed at the destruction of virus-infected cells. The immune disorders in children with CVH B and C from the phase of viral replication and inflammatory activity in the liver was proven. Since the phase of replication and the increase of the activity of inflammation was an increase of CD8+, indicating activation of cytotoxic reactions and causes progressive destruction of hepatocytes. Conclusions: 1. The immune disorders in children with CVH B and C in phase of viral replication are proven. So, there is an increase CD8 +, which indirectly indicates the activation of cytotoxic reactions in the phase of viral replication. With the growth of virus replication activity was significantly intensified the ratio of CD4+/CD8+. This proves that is situ populations of CD4+ could positively regulate the activity of CD8+ at CVH B and C. 2. The increase of the activity of inflammation occurs a significant increase in CD8+ and CD16+, which on the one hand contribute to the elimination of the virus from the microorganism, and the other - causing a progressive lesion of hepatocytes as enhance cytolysis syndrome are established. 3. Further study of the immune status of children of different age groups with CVH B and C supplement will allow immunopathogenesis of the disease, and improve data pathogenetic therapy of diseases.